Effect of buckwheat hull particle-size on bread staling quality. (30th March 2023) - Wang, Lijuan; Li, Yang; Guo, Zicong; Wang, Haoran; Wang, Aili; Li, Zaigui; Chen, Yaoxing; Qiu, Ju
Graphical abstract: Highlights: The effects of fibers at cell and tissue scale on bread staling were investigated. Gas cell structure of tissue-scale fiber enriched bread became coarser and more open. Cell-scale fiber was superior in delaying starch retrogradation and recrystallization. Starch crystallization peak changed from V-type to B-type during bread staling. Cell-scale fiber restricted the loss of water during bread staling. Abstract: The mechanical grinding scale of insoluble dietary fiber has an important influence on bread staling quality. We investigated the effects of buckwheat hull (BWH) powder at tissue-scale (500–100 μm) and cell-scale (50–10 μm) on the physical and structural changes of bread during storage. The addition of tissue-scale BWH had little effect on loaf volume and crumb firmness of bread, while that of cell-scale BWH significantly decreased specific volume and baking loss, and resulted in higher bread firmness, compared with the control (100 % wheat bread). The effect of cell-scale BWH on delaying amylopectin retrogradation and starch recrystallization during bread storage was superior to that of tissue-scale BWH. Tissue-scale BWH made the gas cell structure of the crumb coarse and open, promoting the evaporation of water during storage. BWH at the cell-scale had a stronger water-binding ability than tissue-scale BWH, which restricted the loss of water, inhibiting bread staling.